(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective:1. To assess the QOL during 1st trimester of pregnancy2. To assess the effect of quality of life on birth weight of new born.Methods: An observational research approach with Prospective research design with consecutive sampling technique was used toselect samples. Antenatal woman who had booked at 12 or before 12 weeks of pregnancy with singleton pregnancy were included inthe study. Study conducted after approval of Ethics Committee of Krishna Institute of Medical Sciences Deemed to be UniversityKarad conducted at Krishna Hospital & MRC, Karad Written consent was obtained To assess the quality of life standardizedWHOQOL tool was used with proper permission from concerned authority. Data analysis- Gathered data was analyzed by utilizing theSPSS20 versionRESULTS: Overall perceived QOL score in NBW is significantly high than LBW with Mean ± SD of NBW 4.40±0.49, LBW-4.14±0.57 (t value=2.712, P value=0.0076). Overall perceived health score in NBW and LBW are similar with (t value=1.744, Pvalue=0.837). At Physical domain score in NBW is significantly high than LBW with Mean ± SD of NBW 80.90±11.91, LBW-70.34±11.36 (t value=4.934, P value=<0.0001). At Psychological domain score in NBW is significantly high than LBW with Mean± SD of NBW 80.47±13.07, LBW-75.64±9.18 (t value=2.262, P value= 0.0255). At Social relationships domain score in NBW issignificantly high than LBW with Mean ± SD of NBW 83.31±13.80, LBW-77.76±11.48 (t value=2.347, P value= 0.0205). AtEnvironment domain score in NBW is significantly high than LBW with Mean ± SD of NBW 81.77±10.48, LBW-72.9±7.39 (tvalue=5.175, P value= <0.0001).CONCLUSION: Means score of Quality Of Life during 1st trimesters of pregnancy in mothers who gave birth to Normal Birth Weightbabies was higher than the mothers who gave birth to Low Birth Weight babies.